Adherence to oral anticancer hormonal therapy in breast cancer patients and its relationship with treatment satisfaction: an important insight from a developing country - Amer A. Koni; Bushra A. Suwan; Maisa A. Nazzal; Alaa Sleem; Aiman Daifallah; Majd Hamed allah; Razan Y. Odeh; Sa'ed H. Zyoud (BMC, 2023)
Abstract Background Hormone-positive breast cancer is the most common type and represents a burden in all countries. Treatment satisfaction might be a predictor for adherence, as higher satisfaction with medication encourages patients to adhere appropriately to the medication and, consequently, successfully achieve the treatment goals. The present study evaluated the adherence of women with hormone-positive breast cancer to oral hormonal drugs and correlated it with treatment satisfaction and other sociodemographic and clinical factors. Methods A cross-sectional design was applied. This study included two cancer centers. Data were collected from patients through face-to-face interviews and medical record reviews. The Medication Adherence Scale was adapted to assess medication adherence, and the Treatment Satisfaction Questionnaire for Medication (TSQM) version 1.4 was adopted to measure treatment satisfaction. Results The final analysis included 106 patients, with a mean age ± SD of 51.9 ± 1.2. Approximately 35% were hospitalized in the past year. Current hormonal therapy among cancer patients included letrozole (38.7%), tamoxifen (31.1%), exemestane (17%), and anastrozole (13.2%). The median adherence score was 5.0 [4.8-6.0], and 62.3% adhered fully to their oral hormonal drugs in the past week. The median scores of effectiveness, side effects, convenience, and global satisfaction were 66.67 [61.11.0-72.22], 75.00 [48.44-100.00], 66.67 [66.67-72.22], and 71.43 [57.14-78.57], respectively. A significantly lower adherence score was identified in patients living in camps (p = 0.020). Patients with comorbidities and those who continued on the same hormonal therapy had higher adherence scores, although they were not statistically significant. Multiple linear regression analysis showed that two domains of treatment satisfaction, side effects (p = 0.013) and global satisfaction (p = 0.018), were predictors of adherence to oral hormonal drugs. Conclusions The current study revealed a significant association between treatment satisfaction and adherence to oral hormonal therapy. We recommend creating a specialized scale to measure adherence, considering the psychosocial factors that affect hormonal anticancer medication adherence.